The Healing Attributes of Rosa Damascena - Bhardwaj, Anjali; Juneja, Shalini; Nathani, Sumit (Journal of Neonatal Surgery, 2025)
This research paper investigates the medicinal and therapeutic properties of Rosa damascena, with a particular focus on its essential oil composition, bioactive compounds, and their potential applications in modern healthcare and cosmetics. The study explores the antimicrobial, anti-inflammatory, antioxidant, and anti-aging properties of R. damascena, supported by experimental studies. The essential oils, rich in flavonoids, phenolic acids, and terpenes, demonstrate significant efficacy in treating various health conditions, including digestive issues, stress-related disorders, and skin irritations. Additionally, the research highlights the plant's culinary and therapeutic uses, such as its role in aromatherapy and its application in skincare products. The findings confirm the potential of R. damascena as a valuable source of bioactive compounds with diverse therapeutic benefits. However, the study also emphasizes the need for further clinical trials to fully assess the plant's pharmacological mechanisms and optimize its use in medicinal formulations.